Immunomodulatory Effects of Exercise in Experimental Multiple Sclerosis - Gentile, Antonietta; Musella, Alessandra; De Vito, Francesca; Rizzo, Francesca Romana; Fresegna, Diego; Bullitta, Silvia; Vanni, Valentina; Guadalupi, Livia; Stampanoni Bassi, Mario; Buttari, Fabio; Centonze, Diego; Mandolesi, Georgia (Frontiers in Immunology, 2019)
Multiple Sclerosis (MS) is a demyelinating and neurodegenerative disease. Though a specific antigen has not been identified, it is widely accepted that MS is an autoimmune disorder characterized by myelin-directed immune attack. Pharmacological treatments for MS are based on immunomodulatory or immunosuppressant drugs, designed to attenuate or dampen the immune reaction, to improve neurological functions. Recently, rehabilitation has gained increasing attention in the scientific community dealing with MS. Engagement of people with MS in exercise programs has been associated with a number of functional improvements in mobility, balance and motor coordination. Moreover, several studies indicate the effectiveness of exercise against fatigue and mood disorders that are frequently associated with the disease. However, whether exercise acts like an immunomodulatory therapy is still an unresolved question. A good tool to address this issue is provided by the study of the immunomodulatory effects of exercise in animal model of MS, including the experimental autoimmune encephalomyelitis (EAE), the Theiler’s virus induced-demyelinating disease (TMEV-IDD) and toxic-demyelinating models, cuprizone (CPZ) and lysolecithin (LPC). So far, despite the availability of different animal models, most of the preclinical data have been gained in EAE and to a lesser extent in CPZ and LPC. These studies have highlighted beneficial effects of exercise, suggesting the modulation of both the innate and the adaptive immune response in the peripheral blood as well as in the brain. In the present paper, starting from the biological differences among MS animal models in terms of immune system involvement, we revise the literature regarding the effects of exercise in EAE, CPZ and LPC and critically highlight the advantages of either model, including the so-far unexplored TMEV-IDD, to address the immune effects of exercise in MS.